Digestive ripening yields atomically precise Au nanomolecules. (19th October 2021) - Eswaramoorthy, Senthil Kumar; Dass, Amala
Abstract : Atomically precise Au nanomolecules yielded through digestive ripening establishes that regardless of the pathway, both DR and Brust methods lead to the formation of atomic precise Au NMs. Abstract : Digestive ripening (DR) is a synthetic method where a polydisperse colloid of metal nanoparticles upon refluxing with a free ligand in a high boiling point solvent gives monodisperse nanoparticles. Brust synthesis is known to form atomically monodisperse thiolate protected gold nanoparticles also known as gold nanomolecules (Au NMs). Unlike the Brust method which gives smaller (1–3 nm) atomically precise nanomolecules, DR has been used only for the synthesis of large nanoparticles (>5 nm) with good monodispersity. In thiolate protected gold nanoparticle Brust synthesis, the yellow colored phase transferred Au(iii ) solution is converted to a colorless Au(i ) mixture after the addition of thiol by forming Au–SR, which is then reduced to form black colored Au NMs. However, in DR, by using the same primary chemicals, the two steps were reversed: the mixture was reduced before the addition of thiol. Here we show that in DR, adding thiol after 2 minutes of reduction gives larger particles (5 nm) as reported, whereas adding thiol 30 seconds after reduction results in smaller particles (<2 nm). In this work, for the first time, DR yields atomically precise Au25 (SR)18 and Au144 (SR)60 NMs. This is reported using two aliphatic thiols – hexanethiol and dodecanethiol – as the protecting ligands. DR was also repeated using an aromatic thiol, 4- tert -butyl benzene thiol (TBBT), which yields Au279 (SR)84 NMs consistent with the Brust method, thereby establishing that both DR and Brust methods lead to the formation of atomically precise Au NMs, regardless of the order of thiol addition and reduction steps.